-(y-1)²+y(y-7)при y=-2/3 подскажите с объяснением​

Anastasias223 Anastasias223    2   26.03.2020 19:04    156

Ответы
alexei2016111 alexei2016111  12.10.2020 05:46

ответ:-(у-1)^2+у(у-7)=-у^2+2у-1+у^2-7у=-5у-1

при у=-2/3   -5*(-2/3)-1=10/3-1=10/3-3/3=7/3=2 1/3

Пошаговое объяснение:

ПОКАЗАТЬ ОТВЕТЫ
Varvaralikhtsr1 Varvaralikhtsr1  12.10.2020 05:46

ответ:2  1/3.

Пошаговое объяснение:

-(-2/3-1)²+(-2/3)(-2/3-7).

-(-5/3)²+(-2/3)*(-23/3).

-(25/9)+46/9=21/9=7/3=2 1/3.

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика